Argument structure and syntactic relations : a cross-linguistic perspective - Duguine, Maia; Huidobro, Susana; Madariaga, Nerea (Linguistik aktuell, 2010)
The topic of this collection is argument structure. The fourteen chapters in this book are divided into four parts: Semantic and Syntactic Properties of Event Structure; A Cartographic View on Argument Structure; Syntactic Heads Involved in Argument Structure; and Argument Structure in Language Acquisition. Rigorous theoretical analyses are combined with empirical work on specific aspects of argument structure. The book brings together authors working in different linguistic fields (semantics, syntax, and language acquisition), who explore new findings as well as more established data, but the.